“He’s Just a Wee Laddie”: The Relative Age Effect in Male Scottish Soccer - Dugdale, James H.; McRobert, Allistair P.; Unnithan, Viswanath B. (Frontiers in Psychology, 2021)
Significant structural, developmental and financial constraints exist in Scottish soccer that may predicate a different approach to talent identification and development. To our knowledge, no published reports exist evaluating the prevalence of the relative age effect (RAE) in Scottish soccer players. Consequently, the aim of this study was to investigate the prevalence of the RAE among varied playing levels and ages of male Scottish youth soccer players. Birthdates of male youth players (n = 1,230) from U10-U17 age groups and from playing levels: ‘Amateur’ (n = 482); ‘Development’ (n = 214), and; ‘Performance’ (n = 534), alongside a group of male Scottish senior professional players (n = 261) were recorded and categorised into quartiles (Q1 = Jan-Mar; Q2 = Apr-Jun; Q3 = Jul-Sep; Q4 = Oct-Dec) and semesters (S1 = Jan-Jun; S2 = Jul-Dec) from the start of the selection year. Birthdates were analysed for: (a) each playing level, and; (b) each age group irrespective of playing level. For the varied playing levels examined, a RAE was evident in ‘Development’ and ‘Performance’ playing levels only at youth level. When examining each age group, a RAE was observed in U12-U17 players only. While there was a slight asymmetry favouring Q1 born senior professional players, the RAE was not present within this group of our sample. Results from our study suggest that a bias in selecting individuals born earlier in the selection year may exist within male soccer academy structures, but not at amateur level. The asymmetry favouring chronologically older players at youth but not professional level questions the efficacy of this (un)conscious bias within male Scottish soccer players.